Coumarin isolation and comparative study of biological activities of Pterocaulon alopecuroides DC and Pterocaulon lorentzii Malme - Cristina Mayumi Sasaki; Beatriz Cristina Konopatzki Hirota; Cristina Peitz de Lima; Maria Christina dos Santos Verdam; Cristiane da Silva Paula; Suelen Cristina Chaves; Patrícia Maria Nunes Pavan; Marilis Dallarmi Miguel; Obdulio Gomes Miguel (International Journal of Phytomedicine, 2013)
5-(2,3-Dihidroxy-3-methylbuthyloxy)-6,7-methylenedioxycoumarin was isolated from the chloroform extract of the two Asteraceae species Pterocaulon alopecuroides DC. and Pterocaulon lorentzii Malme. The structure was elucidated through IR and 1H and 13C NMR analyses. The extracts and the isolated compound did not exhibit toxic activity, as determined through the brine shrimp lethality method, and did not interfere with the integrity of erythrocytes, as demonstrated through a hemolytic assay. The antioxidant activities were investigated through three methods. In the phosphomolybdenum test, the ethyl acetate fraction of P. alopecuroides exhibited an antioxidant activity of 137.7% compared with rutin (positive control), and the ethyl acetate fraction of P. lorentzii exhibited an antioxidant activity of 101.7% compared with vitamin C (positive control). The two ethyl acetate fraction also exhibited excellent activity through the DPPH assay: P. alopecuroides and P. lorentzii exhibited IC50 values of 10.74 μg/ml and 7.63 μg/ml, respectively. In the TBARS bioassay, the crude extracts showed the more significant results: IA% 0.419 ± 0.0517 for P. alopecuroides and IA% 0.213 ± 0.0094 for P. lorentzii.